2000
DOI: 10.1016/s0370-2693(00)01232-6
|View full text |Cite
|
Sign up to set email alerts
|

First measurement of antikaon phase-space distributions in nucleus–nucleus collisions at subthreshold beam energies

Abstract: Differential production cross sections of K − and K + mesons have been measured as function of the polar emission angle in Ni+Ni collisions at a beam energy of 1.93 AGeV. In near-central collisions, the spectral shapes and the widths of the rapidity distributions of K − and K + mesons are in agreement with the assumption of isotropic emission. In non-central collisions, the K − and K + rapidity distributions are broader than expected for a single thermal source. In this case, the polar angle distributions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 23 publications
5
72
0
Order By: Relevance
“…and non-central (b = 4.5 ÷ 7.5 fm) (r.h.s) collisions in comparison to the KaoS data from Ref. [5] (Fig. 8) The K − rapidity distributions are slightly overestimated when using only 'free' kaon and antikaon masses.…”
Section: B K ± Spectra From Nucleus-nucleus Collisionsmentioning
confidence: 84%
See 1 more Smart Citation
“…and non-central (b = 4.5 ÷ 7.5 fm) (r.h.s) collisions in comparison to the KaoS data from Ref. [5] (Fig. 8) The K − rapidity distributions are slightly overestimated when using only 'free' kaon and antikaon masses.…”
Section: B K ± Spectra From Nucleus-nucleus Collisionsmentioning
confidence: 84%
“…The in-medium modification of kaon/antikaon properties can be observed experimentally primarily in relativistic nuclear collisions. Indeed, the experimental [3,4,5,6,7] and theoretical studies [8,9,10,11,12,13,14,15,16,17] on K ± production from A+A collisions at SIS energies of 1-2 A·GeV have shown that in-medium properties of kaons have been seen in the collective flow pattern of K + mesons as well as in the abundancy and spectra of antikaons.…”
Section: Introductionmentioning
confidence: 99%
“…A direct measurement of isospin differences of flow observables would highly desirable. [19] and KaoS [20]. Theoretical calculations are given for the isospinindependent part of the kaon potential in the ChPT and OBE models (left), and including the isospin dependent part (right) [17].…”
Section: Proton-neutron Differential Flowmentioning
confidence: 99%
“…E.g.,the dilepton spectra observed from heavy ion collision experiments at the SPS [1,2] are attributed to the medium modifications of vector mesons [3,4,5,6,7], and can not be explained by vacuum hadronic properties. The production of kaons and antikaons as well as their collective flow are attributed to the modifications of their spectral functions in the medium [4,8,9,10,11,12,13,14]. Due to the presence of the light quark/antiquark, the medium modifications of the D (D) mesons can be appreciable in the dense hadronic medium [15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%